Development and Validation of a Nomogram Based on 18F-FDG PET/CT Radiomics to Predict the Overall Survival in Adult Hemophagocytic Lymphohistiocytosis - Yang, Xu; Liu, Jun; Lu, Xia; Kan, Ying; Wang, Wei; Zhang, Shuxin; Liu, Lei; Zhang, Hui; Li, Jixia; Yang, Jigang (Frontiers in Medicine, 2021)
Purpose: Hemophagocytic lymphohistiocytosis (HLH) is a rare and severe disease with a poor prognosis. We aimed to determine if 18F-FDG PET/CT-derived radiomic features alone or combination with clinical parameters could predict survival in adult HLH. Methods: This study included 70 adults with HLH (training cohort n=50; validation cohort n=20) who underwent pre-therapeutic 18F-FDG PET/CT scans between August 2016 and June 2020. Radiomic features were extracted from the liver and spleen on CT and PET images. For evaluation of 6-month survival, the features exhibiting p<0.1 in univariate analysis between non-survivors and survivors were selected. And the least absolute shrinkage and selection operator (LASSO) regression analysis was used to develop a radiomics score (Rad-score). A nomogram was built by multivariate regression analysis to visualize the predictive model for 3-month, 6-month and 1-year survival, while the performance and usefulness of the model were evaluated by calibration curves, receiver operating characteristic (ROC) curves and decision-curves. Results: The Rad-score was able to predict 6-month survival in adult HLH, with areas under receiver operating characteristic curves (AUCs) of 0.927 (95%CI 0.878-0.974) and 0.869 (95%CI 0.697-1.000) in the training and validation cohort, respectively. The radiomics nomogram combining the Rad-score with the clinical parameters resulted in better performance for predicting 6-month survival than the clinical model or Rad-score alone. Moreover, the nomogram displayed superior discrimination, calibration, and clinical usefulness in both cohorts. Conclusions: The newly developed Rad-score is a powerful predictor for overall survival (OS) in adults with HLH. The nomogram has great potential for predicting 3-month, 6-month and 1-year survival, which may timely guide personalized treatments for adult HLH.